The relationship between safety management and patient safety culture in Cancer Treatment Centers - Ali Maher; Mohammad Monfared; Mehrnoosh Jafari (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: Enhancement of patient safety represents a principle objective followed by any health system, and it is necessary to consistently monitor the patient safety culture among nurses. Adopted by health service providers, the patient safety culture is described as the acceptance and maintenance of the patient safety as a common priority and value across the organization, or representation of the common patient safety-related values, beliefs, perceptions, and attitudes among the staff at centers providing health services, as expressed in their behaviors. Given the importance of this topic, the present research investigates the state of safety management in the relationship between safety management and patient safety culture in Cancer Treatment Centers, so as to study the patient safety culture among the personnel at the hospitals.